2006
DOI: 10.1111/j.1364-3703.2006.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

The MAP kinase‐encoding gene MgFus3 of the non‐appressorium phytopathogen Mycosphaerella graminicola is required for penetration and in vitro pycnidia formation

Abstract: SUMMARY In eukaryotes, a family of serine/threonine protein kinases known as mitogen-activated protein kinases (MAPKs) is involved in the transduction of a variety of extracellular signals and in the regulation of growth and development. We identified a MAPK-encoding gene in Mycosphaerella graminicola strain IPO323 with high homology to the orthologous Fus3 gene of Saccharomyces cerevisiae and designated it MgFus3. Early colony development of the MgFus3 mutants during in vitro growth was similar to those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 43 publications
2
76
1
Order By: Relevance
“…While diverse environmental signals can affect dimorphism, the main signaling pathways appear well conserved, with the cAMP-dependent protein kinase A and mitogen-activated protein kinase pathways (Nadal et al, 2008) having major roles. In Z. tritici both of these pathways were shown to affect the dimorphism phenotype (Cousin et al, 2006;Mehrabi and Kema, 2006;Mehrabi et al, 2006a, b;Gohari et al, 2014). It is not known if the yeast-like morphology plays any role in the natural history of Z. tritici.…”
Section: Genetic Architecture Of Tsmentioning
confidence: 99%
See 1 more Smart Citation
“…While diverse environmental signals can affect dimorphism, the main signaling pathways appear well conserved, with the cAMP-dependent protein kinase A and mitogen-activated protein kinase pathways (Nadal et al, 2008) having major roles. In Z. tritici both of these pathways were shown to affect the dimorphism phenotype (Cousin et al, 2006;Mehrabi and Kema, 2006;Mehrabi et al, 2006a, b;Gohari et al, 2014). It is not known if the yeast-like morphology plays any role in the natural history of Z. tritici.…”
Section: Genetic Architecture Of Tsmentioning
confidence: 99%
“…Identification and characterization of candidate genes within QTL confidence intervals Earlier gene disruption studies in the IPO323 reference strain identified 10 genes (MgTpk2, MgGpa1, MgGpa3, MgGpb1, MCC1, MVE1, MgSlt2, MgHog1, MgFus3 and ZtWor1) that affected the yeast/hyphae growth morphology (Cousin et al, 2006;Mehrabi and Kema, 2006;Mehrabi et al, 2006aMehrabi et al, , b, 2009Choi and Goodwin, 2011a, b;Gohari et al, 2014). We did not find any of these genes in the 95% confidence intervals of the dimorphism QTLs identified in our study, indicating that our QTL mapping approach identified novel gene candidates associated with the yeast/hyphae dimorphism in Z. tritici.…”
Section: Genetic Architecture Of Tsmentioning
confidence: 99%
“…In A. nidulans and other filamentous fungi, homologs of FUS3 have been characterized (i.e. Atoui et al, 2008;Chen et al, 2004;Cousin et al, 2006;Di Petro et al, 2001;Jenczmionka et al, 2003;Mey et al, 2002;Moriwaki et al, 2007;Rauyaree et al, 2005;Ruiz-Roldman et al, 2001;Takano et al, 2000;Xu et al, 1996;). Our laboratory has shown that the A. nidulans FUS3 homolog, mpkB, controls sexual development and secondary metabolism (Paoleti et al, 2007;Atoui et al, 2008).…”
Section: Mpkb Signallingmentioning
confidence: 99%
“…22 The Fus3 homolog also plays a critical role in virulence of other phytopathogenic fungi, including A. brassicicola, Bipolaris oryzae, Botrytis cinerea, Claviceps purpurea, C. heterostrophus, Colletotrichum lagenarium, Cryphonectria parasitica, Fusarium spp., Mycosphaerella graminicola, Pyrenophora teres, Stagonospora nodorum and Verticillium dahliae. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The Fus3 homolog (Cek1) is also an important virulence determinant in the opportunistic human pathogen Candida albicans. 38 The AaFus3 gene encoding a homolog of the yeast Fus3-like MAP kinase was cloned and 39 In addition, the Fus3 MAPK-mediated signaling pathway is involved in conidia formation and maturation in A. alternata, since Dfus3 mutant does not produce any conidia.…”
Section: Introductionmentioning
confidence: 99%